KONTRIBUSI PENDAPATAN ASLI DAERAH DAN DANA PERIMBANGAN TERHADAP BELANJA MODAL DAN KINERJA KEUANGAN DAERAH PROVINSI BALI - Ida Bagus Badjra; I Ketut Mustanda; Nyoman Abudanti (Jurnal Akuntansi Indonesia, 2017)
Issues that arise in a decentralized government that is when the allocations are not appropriate in capital expenditure as well as the reception is not optimal (PAD, DBH, DAU, and DAK) that impact on the performance of local government. This study aimed to analyze the effect of revenue (PAD) and Fund Balance to the Capital Expenditure and Financial Performance Bali Provincial. The study population was all over the city /regency in Bali. This research technique using census method. The results showed that capital spending is directly positive and significant impact on the financial performance area, equalization funds directly no significant effect on capital expenditure, the balance funds indirectly positive and significant impact on the financial performance areas, PAD direct significant effect on capital spending PAD indirectly no significant negative effect on the financial performance of the region.